2016
DOI: 10.1016/j.conbuildmat.2016.06.125
|View full text |Cite
|
Sign up to set email alerts
|

Modification of water retention and rheological properties of fresh state cement-based mortars by guar gum derivatives

Abstract: International audienceThe present study examines the influence of chemical composition and structure of guar gum derivatives on water retention capacity (WR) and rheological behavior of fresh state cement-based mortars. The investigation was also completed by adsorption isotherms. For this, original guar gum, three HydroxyPropyl Guars (HPG) and two hydrophobically modified HPGs were selected. The effect of the molar substitution (MSHP) and of hydrophobic substitution (DSAC) was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
2
25
2
1
Order By: Relevance
“…4, Table 3). It has been previously showed that HPGs can also adsorb on mineral surface, and therefore on cement particles and the depleted amount of HPG determined by the depletion method was not the result of physical entrapment of polymer molecules into the inter-particles space during the centrifugation step [20,40]. However, it can be mentioned here that the nature of the interaction, i.e.…”
Section: Adsorption Curves and Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…4, Table 3). It has been previously showed that HPGs can also adsorb on mineral surface, and therefore on cement particles and the depleted amount of HPG determined by the depletion method was not the result of physical entrapment of polymer molecules into the inter-particles space during the centrifugation step [20,40]. However, it can be mentioned here that the nature of the interaction, i.e.…”
Section: Adsorption Curves and Discussionmentioning
confidence: 71%
“…Several studies were devoted to the estimation of the water retention capacity induced by the HPGs and to their mechanism of action [16][17][18][19][20]. The chemical structure of the HPGs, such as the molecular mass, the amount of hydropropyl groups grafted on the backbone, characterized by the MS (MSHP), and the nature of the grafting, appear as crucial parameters for the water retention properties [20,21]. Indeed, these structural parameters affect the dosage necessary to reach the coil overlapping concentration, corresponding to the concentration from which, the isolated polymer coils, existing at low polymer concentration, come into contact.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, agriculture is an immanently important economic driver in South America and Africa with large growth potential. It is therefore reasonable to take a closer look on possible uses of bio-based waste products as construction constituents in countries with large agricultural sector:  Polysaccharides can be excellent precursors for performance enhancing chemical admixtures, that can help reducing the cement in concrete and using cement more efficiently [7][8][9][10][11].  Various ashes of agricultural waste products exhibit pozzolanic or hydraulic properties, provided they are processed adequately.…”
Section: Introductionmentioning
confidence: 99%